Leaders Nearing the End of their Career May Endanger Humanity - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
Older leaders have regularly been recognized along human history as reasonable, cautious, and loyal to their duty to unite the citizens, care for national prosperity, and lead the population safely through dangerous times and evil occasions. Interestingly, such characteristics usually typify also leaders of animal herds, emphasizing the importance of expierence, confidence, and leadership. However, humans also share with the other mammals traits like aggression and violent instincts that were important at the time for survival. One prominent trait is exemplified in the propensity for violence using force to solve conflicts and various disputes.